Evaluation of coastal Antarctic precipitation in MAR3.9 regional and LMDz6 global atmospheric model with ground-based radar observations - Florentin Lemonnier; Alizée Chemison; Hubert Gallée; Gerhard Krinner; Jean-Baptiste Madeleine; Chantal Claud; Christophe Genthon (PANGAEA, 2024)
In the current context of climate change in the poles, one of the objectives of the APRES3 (Antarctic Precipitation Remote Sensing from Surface and Space) project is to characterize the vertical structure of precipitation in order to better simulate it. Nowadays, the precipitation simulated by models in Antarctica is very widespread and overestimated the data. Sensitivity studies have been conducted using two models and compared to the observations obtained at the Dumont d extquotesingleUrville coast station, obtained by a Micro Rain Radar (MRR). The MAR meso-scale model specifically developed for the polar regions and the LMDz/IPSL general circulation model, with zoomed configuration over Dumont d extquotesingleUrville, have been considered for this study. These models being different in resolution and physical configuration, performing an inter-comparison required numerical, dynamic and physical adjustments in LMDz. A sensitivity study was conducted on the physical and numerical parameters of the LMDz model and on the resolution of the MAR with the aim of estimating their contribution to the precipitation simulation. Sensitivity tests with MAR revealed that this model is well adjusted for precipitation modeling in polar climates, this confirming that this model is a reference in polar climate modeling. Regarding LMDz, sensitivity experiments revealed that modifications in the sedimentation and sublimation parameters do not significantly impact precipitation rate. However, dissipation of the LMDz model, which is a numerical process that dissipates spatially excessive energy and keeps the model stable, impacts precipitation indirectly but very strongly. A suitable adjustment of the dissipation reduces significantly precipitation over Antarctic peripheral area, thus providing a simulated profile in better agreement with the MRR observations.